Библейские мотивы в романе Ф.М. Достоевского «Идиот» - Мальцева, Е.Ю. (My University, 2013)
Biblical motives of a novel by Fyodor Dostoevsky «The Idiot». The article examines biblical motives of the novel by Dostoevsky «The Idiot». The techniques of incorporating biblical material into an artistic tissue of the novel are thoroughly examined by author. Functional capacity of biblical layer of the novel is being analyzed.